Application of Dried Mixed Culture (Lactobacillus plantarum, Lactobacillus fermentum and Sacchromyces cereviceae) in maize and sorghum fermentation - Putri, Widya D.R.; Widyaningsih, Tri Dewanti; Ningtyas, Dian Widya (Fakultas Teknologi Pertanian Universitas Brawijaya, 2009)
Whole cereal-based products, i.e maize and sorghum have a beneficial effect on health, but they also contain high level of phytate and tannin that defined as anti-nutrition which could affect protein digestibility. The quality of protein can be improved by fermentation, as natural fermentation or with pure culture. Dried culture containing lactic acid bacteria (Lactobacillus plantarum, Lactobacillus fermentum) and khamir (Saccharomyces cereviceae), is potential for cereal fermentation to decrease anti-nutrition compounds and to increase protein digestibility of cereal based product. The main objective of this research was to know the effect of applying dried mixed culture of L. plantarum, L. fermentum, and S. cereviceae on maize and sorghum flour fermentation, and to determine the effect of maize and sorghum flour fermentation on protein digestibility, antinutrition components, and other chemical and physical characteristics. The result showed that the mixed dried culture increased protein digestibility of fermented maize and sorghum flour, from 48.23% and 38.44% to 89.31% and 91.00%, respectively. Phytic acid content of maize flour decreased 43.14%, and tannin content of sorghum flour decreased 74.84%. Weaning food was made from fermented maize and sorghum flour had energy of 160 kcal for consumption of 40 g/day (for a 6 – 12 month child), and 312.5 kcal for consumption of 76 g/day (for a 13 – 24 month child).Keywords: dried mixed culture, maize fermentation, sorghum fermentation, antinutrition, protein digestibility